2016
DOI: 10.1002/app.43490
|View full text |Cite
|
Sign up to set email alerts
|

Thermally exfoliated graphene oxide reinforced fluorinated pentablock poly(l‐lactide‐co‐ε‐caprolactone) electrospun scaffolds: Insight into antimicrobial activity and biodegradation

Abstract: Three‐dimensional fluorinated pentablock poly(l‐lactide‐co‐ε‐caprolactone)‐based scaffolds were successfully produced by the incorporation of thermally exfoliated graphene oxide (TEGO) as an antimicrobial agent with an electrospinning technique. In a ring‐opening polymerization, the fluorinated groups in the middle of polymer backbone were attached with a perfluorinated reactive stabilizer having oxygen‐carrying ability. The fiber diameter and its morphologies were optimized through changes in TEGO amount, vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Graphene with its unique 2D structure and exceptional physical and chemical properties has attracted the attention of scientists and engineers in various advanced applications such as development of novel polymeric composites with unique properties [15,[48][49][50]. Graphene is one of the strongest materials, having a theoretical Young's modulus of 1060 GPa and an ultimate strength of 130 GPa, and also high specific surface area, which makes it a suitable candidate for nanocomposite production with extended physical and chemical properties [48].…”
Section: Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Graphene with its unique 2D structure and exceptional physical and chemical properties has attracted the attention of scientists and engineers in various advanced applications such as development of novel polymeric composites with unique properties [15,[48][49][50]. Graphene is one of the strongest materials, having a theoretical Young's modulus of 1060 GPa and an ultimate strength of 130 GPa, and also high specific surface area, which makes it a suitable candidate for nanocomposite production with extended physical and chemical properties [48].…”
Section: Graphenementioning
confidence: 99%
“…Page 434 nanomaterials such as carbon black, which restricts their antimicrobial activities through the mentioned mechanism. In addition, GO shows higher cytotoxicity compared with rGO; this is because of its higher dispersibility in aqueous media, and presence of active surface functional groups, which promote the possibility of direct contact with cells and inducing higher intracellular oxidative stress [49]. Contrarily, some studies showed higher toxicity of rGO is correlated with its thinner structure in the absence of oxygen functional groups (0.34 nm) compared with that of GO (1 nm), which creates sharper edges to damage the cell membrane easily [58,59].…”
Section: Graphenementioning
confidence: 99%
“…There is a large difference in bulk properties of PLA with PCL . Therefore, their blends and copolymers were suggested for creation of new biomaterials with tailored mechanical, thermal, and viscoelastic and biodegradation properties suitable for the given environmental or physiological conditions …”
Section: Introductionmentioning
confidence: 99%